Rapid and direct quantification of the SARS-CoV-2 virus with an ultrasensitive nanobody-based photonic nanosensor. Issue 5 (29th June 2022) - Ruiz-Vega, Gisela; Soler, Maria; Estevez, M. Carmen; Ramirez-Priego, Patricia; Pazos, Martalu D.; Noriega, María A.; Margolles, Yago; Francés-Gómez, Clara; Geller, Ron; Matusali, Giulia; Colavita, Francesca; di Caro, Antonino; et al.
Abstract : An innovative nanophotonic sensor using bioengineered nanobodies as receptors enables ultrasensitive COVID-19 detection and viral load determination in a 15 min assay without sample pretreatments. Abstract : The coronavirus (CoV) disease 2019 (COVID-19) is expected to become endemic in the coming years, meaning that the worldwide society shall be prepared to routinely manage the highly contagious respiratory SARS-CoV-2. A rapid and early diagnosis of the SARS-CoV-2 infection is crucial for controlling the spread of the disease, interrupting the transmission chain, and providing timely medical attention to patients. We introduce an innovative nanophotonic biosensor for the quantitative detection of viral particles in less than 20 minutes total assay time. The nanosensor, based on the bimodal waveguide (BiMW) interferometric technology, has been functionalized with novel bioengineered nanobodies (Nb) targeting the SARS-CoV-2 receptor-binding domain (RBD). Our approach relies on the direct capture of the viral particles, and the optimized methodology allows the detection of the SARS-CoV-2 virus with outstanding sensitivity, below 200 TCID50 per mL, being able to provide accurate viral load determination within a broad dynamic range (10 2 –10 6 TCID50 per mL). Both the nanobodies and the sensor nanotechnology can be produced at a large scale with highly-efficient cost-effective procedures, and they are being integrated into a user-friendly point-of-care device for multiplexed and decentralized operation. The implementation of this unique biosensor in primary care assistance, hospitals, pharmacies, or private laboratories could greatly aid in the relief and descongestion of the sanitary systems and the clinical and social management of COVID-19.